The clinicopathological characteristics and prognosis of diabetic nephropathy in Tibetan area - HE Yan; WANG Yan; CIREN Luobu; ZHANG Lei; A Yong; LI Guo-liang; SUOLANG Quzhen; DANG Zong-hui (Linchuang shenzangbing zazhi)
Objective To analyze and summarize the clinicopathological characteristics and prognosis of diabetic nephropathy(DN)in Tibetan area.Methods Patients with biopsy-confirmed DN at Tibet Autonomous Region People’s Hospital from April 2016 to December 2019 were recruited in this study.Their clinical,pathological and follow-up data were retrospectively analyzed.All the patients were divided into 4 groups based on the pathological types of DN to compare between groups.In addition,they were divided into 2 groups based on occurrence of outcome event to analyze,where the outcome event was defined as need for renal replacement treatment or death.Results A total of 48 patients were enrolled,including 37 males(77.08%),with an average age of(53.60±10.22) years.In time of renal puncture biopsy,the mean 24-hour urinary protein was(4.59±2.19)g and the mean serum creatinine was(167.87±110.79)μmol/L.There were 7 cases with pathological type IIa,6 cases with pathological type IIb,30 cases with type III,and 5 cases with type IV in terms of DN pathological typing.Patients with type III had higher urinary protein levels,and patients with type IV had higher serum uric acid levels.Mean follow-up duration was(10.70±8.64) months.During the follow-up period,6 patients received renal replacement therapy(RRT)and 12 patients died.The median event-free survival time was 15 months;the 1-year and 2-year event-free cumulative survival rate were 67.8% and 33.1%,respectively.The patients with outcome events had an older age,a lower serum albumin level and lower renal functions in time of renal puncture biopsy.Conclusions DN patients in Tibet have an early onset age,late timing of kidney biopsy,and poor prognosis.Local physicians should conduct renal biopsy for those patients,and enhance education and management of patients,so as to improve the prognosis.